PENGARUH SUPERVISI, MONITORING, EVALUASI PELAPORAN (SMEP) TERHADAP EFEKTIVITAS PELAKSANAAN PROGRAM TP PKK DI KABUPATEN OKU - Arief Budiman; Yunita Sari; Rini Efrianti (LPPM STIE Muhammadiah Bandung, 2026)
Family Welfare Empowerment (PKK) is an organization that involves the participation of women and men in efforts to realize prosperous families. Supervision, Monitoring, and Evaluation of Reporting (SMEP) in the PKK's core programs is one effort aimed at ensuring the smooth and orderly administration of the PKK at the village level. The research results indicate that supervision, evaluation, and reporting (SMEP) simultaneously influence the effectiveness of the implementation of PKK programs in OKU Regency. Monitoring, however, has no effect on the effectiveness of PKK programs in OKU Regency. Supervision (X1), Monitoring (X2), and Evaluation and Reporting (SMEP) have a partial effect, while the remaining 17% is influenced or explained by other variables not included in this research model.